MEMBANGUN PEMAHAMAN LITERASI DIGITAL SISWA SDN 1 CILOLOHAN: PEMANFAATAN DAN ETIKA BERMEDIA SOSIAL - Agustina, Nanda; Mulyani, Indah; Aurelia, Priscilla Windy; Hartini, Yulaiva; Azani, Nadia; Afifah, Siti Zahra; Nuraidah, Iis Jihan; Kamila, Silfa Fauziah; Nursabani, Nayla; Aurelia, Fidya Azhra; Hamdan, Ahmad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
In the digital era, various conveniences in everyday life include the use of social media, especially for elementary school students who have started to actively use social media. However, ignorance of digital ethics and security can have negative impacts such as addiction, cyberbullying, and the spread of fake news. Therefore, early introduction to the positive and negative impacts of social media is needed. The main focus of the study is to provide education to Cilolohan students about the importance of social media ethics and the benefits of social media in education. The implementation method used is to provide direct education through class activities, discussions and simulations of using social media wisely. The materials presented include, introduction to social media, positive and negative impacts, and good ethics in using social media. The results of this activity, we saw a significant increase in students' understanding of how to use social media safely and wisely. They are better able to recognize the risks that can occur in cyberspace and understand how to maintain privacy and behave politely on digital platforms. With an easy-to-understand approach, it is hoped that students can apply the knowledge gained in using social media more wisely, be able to increase awareness and responsibility for digital literacy, and create a safe and productive digital environment.